Effect of 3-methoxysalicylaldehyde on transparency and mechanical properties of EP modified with aminopyridine-based DOPO derivative. (May 2023) - Chen, Rui; Dongmei, Bao; Jiang, Jiaye; Sun, Chuanbo; Chen, Han; Zhang, Min
Two effective flame retardant additives hsalaminopyridine phosphaphenanthrene (HAD) and methoaminopyridine phosphaphenanthrene (MAD) were respectively prepared with DOPO, aminopyridine, salicylaldehyde and 3-Methoxysalicylaldehyde. Subsequently, HAD and MAD was added into epoxy resin (EP) respectively, and flame retardancy of EP/HAD and EP/MAD thermosets were dramatically enhanced. The result of cone calorimeter (CC) test revealed that both HAD and MAD showed perfect smoke suppression performance. In respect of transmittance and mechanical properties, there was a huge difference between HAD and MAD. The introduction of HAD dramatically harmed transmittance and mechanical properties of EP, while, EP/10%MAD was transparent and nearly possessed the same mechanical properties with pure EP.